2013
DOI: 10.5430/jnep.v3n7p99
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of endotracheal-suctioning practices of critical-care nurses – An observational correlation study

Abstract: Background: Endotracheal-suctioning (ETS) is a procedure that may constitute a risk factor for ventilator-associated pneumonia (VAP) by increasing microbial colonization of the lower airway. Unsafe ETS practices have been observed worldwide during recent years. Because of adverse reactions, practioners need to take all necessary precautions to ensure patient safety and a high quality of nursing care. The aim of the present study was to evaluate critical-care nurses' performance in relation to current recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 18 publications
5
34
0
3
Order By: Relevance
“…Infectioncontrol practices (e.g., hand hygiene 72.2%, protection of practioners and patients from secretions as well as adequate disposal of the used catheter 67.7% and gloves100.0%, and maintenance of the sterility of the suction catheter) are crucial elements in the prevention of cross-infections and transmission of pathogens via hands or equipment. 15,16 This result agrees with that of the other researcher who reported that In relation to the use of personal protective equipment (PPE), similarly to what is found in the literature high adherence to the use of gloves was ascertained (92%) as was regular use of the mask and apron (72% and 60%), although there was no adherence to the use of eye protection (0%). Studies have shown that the nurses themselves, in spite of recognizing the importance of the use of PPE, do not use it appropriately when under taking the ETS procedure.…”
supporting
confidence: 80%
“…Infectioncontrol practices (e.g., hand hygiene 72.2%, protection of practioners and patients from secretions as well as adequate disposal of the used catheter 67.7% and gloves100.0%, and maintenance of the sterility of the suction catheter) are crucial elements in the prevention of cross-infections and transmission of pathogens via hands or equipment. 15,16 This result agrees with that of the other researcher who reported that In relation to the use of personal protective equipment (PPE), similarly to what is found in the literature high adherence to the use of gloves was ascertained (92%) as was regular use of the mask and apron (72% and 60%), although there was no adherence to the use of eye protection (0%). Studies have shown that the nurses themselves, in spite of recognizing the importance of the use of PPE, do not use it appropriately when under taking the ETS procedure.…”
supporting
confidence: 80%
“…Slaugytojas turi turėti pakankamai kompetencijos nuspręsti apie sekreto išsiurbimo iš tracheostomos vamzdelio būtinumą. Užsienio šalyse atlikti tyrimai rodo, kad slaugytojai, atlikdami tracheostomos priežiūrą, ne visada remiasi įrodymais pagrįsta praktika [17][18][19][20][21]. Day T., Iles N., Griffiths P. (2009) teigimu, nepakanka įvertin-ti slaugytojų teorines žinias, nes jos gali prastai atspindėti praktiką [19].…”
Section: įVadasunclassified
“…stebėtų atvejų siurbimo slėgis buvo 80-150 mmHg [21]. Airijoje (2008) atlikto tyrimo metu sekreto siurbimo slėgiai viršijo rekomenduojamus slėgius ir svyravo 230 -450 mmHg [20].…”
Section: Diskusijaunclassified
“…It was a developed tool by the researcher after reviewing the related literature (2,3,10,(21)(22)(23) . It was used to gather data of cardiorespiratory parameters to compare between actual routine method practiced by nurses in ICU and guidelines based method that are restricted to evidenced based recommendations.…”
Section: Toolmentioning
confidence: 99%
“…The tool was developed by the researcher based on reviewing the relevant literature (2,3,10,(21)(22)(23) . The tool was reviewed for content validity, by professors in the following fields: critical care nursing, critical care medicine, anaesthesia and medical biostatistics.…”
Section: Toolmentioning
confidence: 99%